031 Bed block – a game to help understand patient flow. Issue 12 (21st November 2019) - Edwards, Sarah; Parkinson, Leesa
Abstract : Background: Patient flow is crucial for patient safety, and for health services and the emergency departments(ED) within them to function. Poor patient flow is associated with increased mortality and morbidity. However, the concept of patient flow was not previously formally taught to all health care professionals (HCP) in our organisation. We developed a fun educational resource to be used with multidisciplinary groups to demonstrate the principles and pitfalls of patient flow in a hospital system. Method and results: Our board game is a collaborative team game for 2–10 players and consists of a hospital with an ED, medical ward, surgical ward and intensive care. The game lasts around 45 minutes, during which the team aims to play through 24 hours in the hospital. The aim is to end the game with fewer patients in the hospital than at the start, without generating too many patient flow safety incidents. Pressure is added to the system by events such as bank holidays, norovirus outbreaks or failure of equipment. During play testing of the game, 90 different HCPs have provided written feedback. Conclusions: 95% of people found that they were more confident, and understood the importance of patient flow following the game. Common themes learnt from the game include the importance of team work, understanding the bigger picture and understanding the pressures in other parts of the hospital. Specific quotes include 'would like to have played for longer', 'this game should be made available for the public, as it might help reduce ED attendances', 'great way of demonstrating the importance of team work'. This early testing of the game has shown how Bed Block can educate around patient flow. Further work is needed to explore the other educational opportunities from this work and if it impacts clinical practice.